A Membrane-Bound NAC-Like Transcription Factor OsNTL5 Represses the Flowering in Oryza sativa - Guo, Siyi; Dai, Shaojun; Singh, Prashant K.; Wang, Hongyan; Wang, Yanan; Tan, Jeanie L. H.; Wee, Wanyi; Ito, Toshiro (Frontiers in Plant Science, 2018)
In spite of short day nature, rice (Oryza sativa) shares a conserved photoperiodic network for flowering control with long day plants like Arabidopsis thaliana. Flowering or heading is an important agronomic trait in rice. NAC transcription factors are well conserved and one of the largest families of plant transcription factors. However, their function in flowering or heading time is not well known yet. A preferential expression of a membrane-bound NAC-like transcription factor OsNTL5 in developing leaves and panicles of rice indicated to us its putative role in flowering. To examine its fuction, three independent constructs was generated, one with a deletion in the C terminus membrane-spanning domain (OsNTL5∆C), OsNTL5∆C fused with the SRDX transcriptional repressor motif and OsNTL5∆C used with the VP16 activation domain under the Ubiquitin promoter to produce the overexpressing lines OsNTL5∆C, OsNTL5∆C-SRDX and OsNTL5∆C-VP, respectively in rice. The OsNTL5∆C-VP line showed an early-flowering phenotype. In contrast to this, the plants with OsNTL5∆C and OsNTL5∆C-SRDX showed a very strong late-flowering phenotype, suggesting that OsNTL5 suppresses flowering as a transcriptional repressor. The protein subcellular localization assay suggested that N-terminal part of the OsNTL5 is localized to the nucleus after the protein is cleaved from its membrane-spanning domain at the C-terminal end and functions as a transcription factor. Expression of flowering genes responsible for day length signals such as Early Heading Date 1 (Ehd1), Heading Date 3a (Hd3a) and Rice Flowering Locus T1 (RFT1) was significantly changed in the overexpression lines of OsNTL5∆C-VP, OsNTL5∆Cand OsNTL5∆C-SRDX as analyzed by Quantitative Real-time PCR. ChIP-qPCR and rice protoplasts assays indicate that OsNTL5 directly binds to the promoter of Ehd1 and negatively regulates the expression of Ehd1, which shows antagonistic photoperiodic expression patterns of OsNTL5 in a 24-h short day (SD) cycle. Hence in conclusion, the NAC-like transcription factor OsNTL5 functions as a transcriptional repressor to suppress flowering in rice as an upstream factor of Ehd1.